2002
DOI: 10.1002/jcb.10158
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock mediated modulation of protein kinase CK2 in the nuclear matrix*

Abstract: Nuclear matrix, a key structure in the nuclear framework, appears to be a particularly responsive target during heat shock treatment of cells. We have previously shown that nuclear matrix is a preferential target for protein kinase CK2 signaling in the nucleus. The levels of CK2 in the nuclear matrix undergo dynamic changes in response to altered growth status in the cell. Here, we have demonstrated that CK2 targeting to the nuclear matrix is profoundly influenced by treatment of the cells to temperatures high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
(37 reference statements)
4
19
0
Order By: Relevance
“…It has been previously noticed that substrates of CK2 reside in the cytoplasm as well as in the nucleus and, that particularly the translocation of the CK2 a 0 subunit from the cytoplasm into the nucleus is observed under various cellular stress conditions, such as heat shock, UV-light or ionizing irradiation [61][62][63]. Accordingly, we were here able to detect APRIL-specific kinase activity also in the cytoplasmic and the nuclear compartment of activated T cells (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been previously noticed that substrates of CK2 reside in the cytoplasm as well as in the nucleus and, that particularly the translocation of the CK2 a 0 subunit from the cytoplasm into the nucleus is observed under various cellular stress conditions, such as heat shock, UV-light or ionizing irradiation [61][62][63]. Accordingly, we were here able to detect APRIL-specific kinase activity also in the cytoplasmic and the nuclear compartment of activated T cells (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Although more than 300 substrates of CK2 have been identified to date, little is known about the spatiotemporal substrate specificity of the different holoenzyme complexes, which contain various combinations of two individual catalytic subunits derived from the respective a, a 0 and a 00 isoforms, and a dimer of two non-catalytic, presumably regulatory b subunits [42,59,60]. It therefore appears that the myriad of regulatory effects caused by CK2 is reflected in a large and, with respect to its subunit composition, highly diverse population of holoenzymes.It has been previously noticed that substrates of CK2 reside in the cytoplasm as well as in the nucleus and, that particularly the translocation of the CK2 a 0 subunit from the cytoplasm into the nucleus is observed under various cellular stress conditions, such as heat shock, UV-light or ionizing irradiation [61][62][63]. Accordingly, we were here able to detect APRIL-specific kinase activity also in the cytoplasmic and the nuclear compartment of activated T cells (Fig.…”
supporting
confidence: 62%
“…To provide a more direct confirmation of the role of CK2 as a suppressor of apoptosis we demonstrated that forced overexpression of CK2 prior to treatment of cells with etoposide or diethylstilbestrol strongly protected them against apoptosis (Guo et al, 2001). Analogous observations based on heat shock treatment of cells supported the role of CK2 in promoting cell survival Davis et al, 2002), and subsequent studies employing radiation or UV treatment of cells have made similar observations (Kato et al, 2003;Yamane and Kinsella, 2005). It was previously suggested that CK2 may be involved in phosphorylation of ser-392 induced by UV damage of DNA (Keller et al, 2001).…”
Section: Ck2 and Cell Deathmentioning
confidence: 76%
“…Conversely, in these animals, administration of a single dose of androgen resulted in rapid and extensive shuttling of CK2 to the nuclear matrix associated with cell growth and suppression of apoptosis . CK2 also suppresses apoptosis in prostate and other cells in response to heat shock and radiation Davis et al, 2002;Yamane and Kinsella, 2005]. More recently, we and others have demonstrated that CK2 can suppress receptor-mediated apoptosis such as that mediated by interaction of TNF-a, TRAIL, and FasL with the death receptors in prostate cancer cells [Wang et al, 2005a[Wang et al, , 2006 and other cancers [Ravi and Bedi, 2002;Izeradjene et al, 2005].…”
Section: Ck2 Signal In Normal Prostate and Prostate Cancermentioning
confidence: 97%